Quality of Care for Patients With Multiple Sclerosis—A Review of Existing Quality Indicators - Kraft, Anna Kristina; Berger, Klaus (Frontiers in Neurology, 2021)
Background: The care of patients with multiple sclerosis (MS) calls for a lifelong guidance and treatment and results in a high resource utilization. Therefore, strategies for the assessment and improvement of the care process are crucial. Quality indicators have become a widely used instrument to determine quality in many areas of the healthcare system. The currently available sets of indicators for the quality of MS care are summarised in this review. Methods: A literature search was conducted for reports that include statements on quality indicators for the care of people with MS. For the determination of the strength of the underlying evidence of the identified publications appropriate criteria of the PRISMA and AGREE-Statements were used. A further prioritisation of the eligible indicators was based on the internal grading by the initial authors. Results: Of the 465 included records in the search, 6 sources were finally identified, 3 demonstrating a high and the others a medium strength of evidence. In total, these 6 reports described 226 quality indicators for the treatment of MS. 147 of them were further included in the assessment due to the scope of this article. Among the 101 indicators that originated from reports with a high strength of evidence, six also had a high initial internal grading. These six identified quality indicators describe five important characteristics of a high quality care of MS. Conclusion: The search led to a scientifically evident set of six quality indicators for the assessment of care for patients with MS. These should be seen as starting points in the development of comprehensive sets of quality indicators in MS that addresses the individual objective of their use.